Group A Streptococcus encounters with host macrophages - Valderrama, J Andrés (Future Microbiol, 2018)
Group A Streptococcus (GAS) is a leading human bacterial pathogen with diverse clinical manifestations. Macrophages constitute a critical first line of host defense against GAS infection, using numerous surface and intracellular receptors such as Toll-like receptors and inflammasomes for pathogen recognition and activation of inflammatory signaling pathways. Depending on the intensity of the GAS infection, activation of these signaling cascades may provide a beneficial early alarm for effective immune clearance, or conversely, may cause hyperinflammation and tissue injury during severe invasive infection. Although traditionally considered an extracellular pathogen, GAS can invade and replicate within macrophages using specific molecular mechanisms to resist phagolysosomal and xenophagic killing. Unraveling GAS–macrophage encounters may reveal new treatment options for this leading agent of infection-associated mortality.